THE EFFECTIVENESS OF USING WORD WALL IN TEACHING SIMPLE PRESENT TENSE AT THE FIRST YEAR STUDENTS OF JUNIOR HIGH SCHOOL 1 PARIGI - Rahmat Syam (Universitas Islam Negeri Alauddin Makassar, 2015)
This research is about the effectiveness of using word wall in teaching simple present tense at the first year students of Junior High School 1 Parigi. The study tried to answer this problem: “Is the word wall effective to be used in teaching simple present tense?”. The objective of the research was to find out the effectiveness of word wall in teaching simple present tense at the first year students of Junior High School 1 Parigi. This research used quasi-experimental design. The population of this research was the first grade students of Junior High School 1 Parigi in academic year 2014/2015. The total number of the population was 48 students. The sample of the research was selected by using total sampling technique. They were divided into two classes, one of the two classes was experimental class and the other became the controlled class. The data were collected through test. After the treatment, the students’ achievement from the pre-test to the post test has improved highly. It can be seen that, the improvement of their score from the pre-test till the post test. The mean score of the pre-test for the controlled class is 42.50, but it has increased to 68.95 at the post test. The mean score of the pre-test for the experimental class is 48.33, but it has increased to 80.20 at the post test. It means that, the experimental class better than the controlled class. World wall has some advantages for the learning process, such as the colorful design of the word wall which could activate the student’s thinking process and students will not be bored and passive in class because they will interact with the word wall. Based on the data above, the researcher concludes that word wall is effective to be used in teaching simple present tense. English teachers should explore more methods that could be used to teach simple present tense.